2011
DOI: 10.1371/journal.pcbi.1002313
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vulnerability of Human Ventricle to Re-entrant Excitation in hERG-linked Variant 1 Short QT Syndrome

Abstract: The short QT syndrome (SQTS) is a genetically heterogeneous condition characterized by abbreviated QT intervals and an increased susceptibility to arrhythmia and sudden death. This simulation study identifies arrhythmogenic mechanisms in the rapid-delayed rectifier K+ current (IKr)-linked SQT1 variant of the SQTS. Markov chain (MC) models were found to be superior to Hodgkin-Huxley (HH) models in reproducing experimental data regarding effects of the N588K mutation on KCNH2-encoded hERG. These ionic channel mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(129 citation statements)
references
References 54 publications
(107 reference statements)
14
115
0
Order By: Relevance
“…The authors reported that the mutation accelerated the ventricular repolarization, shortened the AP duration and the effective ventricular RP while increasing electrical heterogeneity at some local areas, leading to increased risk of re‐entrant arrhythmia. Shortening of the RP was associated with a reduction of the tissue size required to sustain re‐entrant circuits in both 2 and 3 dimensions 26. On the basis of these results, a shortening of ventricular RP may be directly correlated to an increased risk of ventricular arrhythmia in SQTS, although shorter RPs were not linked to the induction of ventricular fibrillation nor to the outcome in our study.…”
Section: Discussionsupporting
confidence: 47%
“…The authors reported that the mutation accelerated the ventricular repolarization, shortened the AP duration and the effective ventricular RP while increasing electrical heterogeneity at some local areas, leading to increased risk of re‐entrant arrhythmia. Shortening of the RP was associated with a reduction of the tissue size required to sustain re‐entrant circuits in both 2 and 3 dimensions 26. On the basis of these results, a shortening of ventricular RP may be directly correlated to an increased risk of ventricular arrhythmia in SQTS, although shorter RPs were not linked to the induction of ventricular fibrillation nor to the outcome in our study.…”
Section: Discussionsupporting
confidence: 47%
“…The parameters of I Kr equations in the original model were replaced with a Markov chain (MC) model of the wildtype (WT) and N588K I Kr [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…The conductance of IKr was chosen based on the APD prolongation observed under experimental IKr block in the human ventricles [12], and the conductances of IKs and IK1 adjusted accordingly. An IKr scaling factor ratio of 1.5:1 in epicardial (EPI) to endocardial (ENDO) cells, respectively, was applied as suggested in the study of Adeniran et al [4], in order to generate a tall, symmetrical T-wave in the pseudo-ECG of the SQT1 phenotype, as seen clinically [2].…”
Section: Model Developmentmentioning
confidence: 99%
“…Eq (2) was discretised in space using the finite difference method and a spatial step of 0.15 mm. The 1D transmural model of human ventricle had a size of 15 mm, comprising 25 ENDO, 35 MCELL, and 40 EPI cells, with isotropic diffusion except for a 5-fold decrease in D at the MCELL:EPI border, as described in [4]. A stimulus was applied at the endocardial surface, eliciting a plane wave which propagated transmurally towards the epicardial surface.…”
Section: Tissue Simulationsmentioning
confidence: 99%
See 1 more Smart Citation